Independensi Pengawas Internal dan Eksternal Birokrasi Publik Serta Implikasinya Terhadap Good Governance - Gilang Iskandar; Edi Pranoto (Fakultas Hukum Universitas Islam Batik Surakarta, 2026)
This study examines the level of independence of internal and external oversight in the administration of public bureaucracy and its implications for the implementation of good governance principles. Oversight serves as a fundamental instrument in a rule of law state to limit the exercise of power and ensure administrative accountability. Although the legal framework regulates the roles of the Government Internal Supervisory Apparatus and external oversight institutions, oversight practices continue to face structural, cultural, and authority-related constraints that undermine independence. This research employs a normative juridical method using statutory and conceptual approaches. The findings indicate that weak oversight independence reduces the effectiveness of administrative control, increases the risk of maladministration, and hinders the consistent application of good governance. Strengthening regulatory frameworks, reforming oversight institutions, and improving bureaucratic culture are therefore essential to ensure objective and integrity-based oversight.